Technological innovation and the bank lending channel of monetary policy transmission - Iftekhar Hasan; Xiang Li; Tuomas Takalo (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This paper studies whether and how banks' technological innovations affect the bank lending channel of monetary policy transmission. We first provide a theoretical model in which banks' technological innovation relaxes firms' earning-based borrowing constraints and thereby enlarges the response of banks' lending to monetary policy changes. To test the empirical implications, we construct a patent-based measurement of bank-level technological innovation, which can specify the nature of technology and tell whether it is related to the bank's lending business. We find that lending-related innovations significantly strengthen the transmission of the bank lending channel.
urn:nbn:fi-fe20231220156018
Keywords: E52; G21; G23; 330; Innovation; FinTech; Monetary Policy Transmission; Bank Lending Channel